2017
DOI: 10.1007/s40881-017-0045-y
|View full text |Cite
|
Sign up to set email alerts
|

Emirati women do not shy away from competition: evidence from a patriarchal society in transition

Abstract: We explore gender attitudes towards competition in the United Arab Emirates -a traditionally patriarchal society which in recent times has adopted numerous policies to empower women and promote their role in the labor force. The experimental treatments vary whether individuals compete in single-sex or mixed-sex groups. In contrast to previous studies, women in our sample are not less willing to compete than men. In fact, once we control for individual performance, Emirati women are more likely to select into c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 50 publications
3
28
2
Order By: Relevance
“…As a robustness check, we did the comparison between athletes and non-athletes separately by gender. Since men have been found to be more competitive than women in many student populations (for a review, see Dariel et al, 2017), the difference in preferences for competition reported above could be driven by differences in the fraction of men and women in the two populations (32% of the athletes are women while 54% of the non-athletes are women). In the lower part of Table 3, we show the summary statistics of the answer to Q4 for men and women.…”
Section: Resultsmentioning
confidence: 99%
“…As a robustness check, we did the comparison between athletes and non-athletes separately by gender. Since men have been found to be more competitive than women in many student populations (for a review, see Dariel et al, 2017), the difference in preferences for competition reported above could be driven by differences in the fraction of men and women in the two populations (32% of the athletes are women while 54% of the non-athletes are women). In the lower part of Table 3, we show the summary statistics of the answer to Q4 for men and women.…”
Section: Resultsmentioning
confidence: 99%
“…This is considered an important part of the country's strategy to become among the countries at the forefront of women's empowerment (Al Serkal, 2015). As a testimony to this commitment, the government established a UAE "Gender Balance Council" charged with promoting equality and opportunities for women in the labour market (Al Serkal, 2015;Dariel et al, 2017;UAE government, 2017). Resulting from this, major improvements on women's involvement in administration have followed.…”
Section: Introductionmentioning
confidence: 99%
“…Resulting from this, major improvements on women's involvement in administration have followed. For instance, currently nine of the 28 ministers in the UAE government are females (Dariel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although Maasai men choose to compete twice as often as women, the opposite result was observed in the Khasi population. Dariel, Kephart, Nikiforakis, and Zenker () revealed that Emirati women are more likely to select into competition than men. Jung and Vranceanu () reveal that the well‐being of Korean women improves after being exposed to competitive compensation in the lab, while the reverse is observed for French women.…”
Section: Resultsmentioning
confidence: 99%